Meaningful Work and Organizational Citizenship Behavior: The Moderating Role of Organizational Culture among High School Teachers - Surya, Eka Putri Amelia; Putra, Rahman Pranovri; Syahti, Maghriza Novita (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aimed to examine the effect of meaningful work on organizational citizenship behavior and the moderating role of organizational culture among senior high school teachers. A quantitative approach with a survey design was employed, involving 49 teachers selected through total sampling. Data were collected using psychological instruments that met established validity and reliability criteria and were analyzed using Moderated Regression Analysis (MRA). The results showed that meaningful work had a positive and significant effect on organizational citizenship behavior (B = 0.482; p < 0.001). Organizational culture also had a positive and significant effect on organizational citizenship behavior (B = 0.365; p = 0.003). Furthermore, the interaction between meaningful work and organizational culture was significant (B = 0.271; p = 0.032), indicating that organizational culture moderated the relationship between meaningful work and organizational citizenship behavior. The model explained 39.8% of the variance in organizational citizenship behavior (R² = 0.398). These findings indicate that the positive effect of meaningful work on organizational citizenship behavior becomes stronger in organizational environments characterized by supportive organizational cultures. This study contributes to a better understanding of teachers’ work behavior by integrating individual motivational and organizational contextual factors. Keywords: meaningful work, organizational citizenship behavior, organizational culture, teachers